Модель персоналізації навчального процесу через інтеграцію LLM у вебзастосунок із динамічною генерацією пояснень - Янко, Аліна Сергіївна; Мизюра, Михайло Сергійович; Yanko, Alina; Myziura, Mykhailo (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Об’єктом дослідження є персоналізація навчальної взаємодії у вебзастосунках на основі великих мовних моделей (LLM) як адаптивного пояснювального ядра. Предметом – модель динамічної генерації роз’яснень, що адаптує складність та стиль викладу до когнітивного профілю та історії помилок студента. Метою роботи є теоретичне обґрунтування та розвиток моделі персоналізації навчального процесу через інтеграцію LLM у структуру вебзастосунку для створення динамічного циклу генерації індивідуальних пояснень із забезпеченням безперервного зворотного зв’язку. Наукова новизна полягає у поєднанні когнітивного профілювання та оркестрування промптів, що враховує структуру помилок, темп діяльності та ознаки рефлексії. Практична значущість підтверджується можливістю вбудовування запропонованої моделі у наявні LMS/EdTech-платформи, скороченням часу на формування пояснення та підвищенням приросту навчальних результатів у контрольованому експерименті. /// EN: The rapid integration of generative artificial intelligence into the educational process fundamentally changes the interaction within the “teacher – learning material – student” triad. In digital courses, the most prominent problem remains the heterogeneity of student groups, where learners start with different knowledge backgrounds, master new material at different paces, and utilize various cognitive strategies. This study aims to theoretically substantiate and develop a personalization model for the educational process through the integration of Large Language Models (LLMs) into the structure of a web application to create a dynamic cycle for generating individualized explanations. The focus is on overcoming the “2 Sigma Problem” by providing automated tutoring support that matches the effectiveness of one-to-one human instruction. Methodology. The proposed model describes the learner through a multidimensional cognitive vector v(t), which includes domain knowledge, procedural competence, reflectiveness, motivational stability, and a cognitive load indicator. A recurrent rule for updating the cognitive profile is established, using a hybrid evaluation scheme: micro-tests, behavioral logs, and dialogue analysis. The dynamic complexity of explanations is determined by an optimization criterion L, which balances penalty coefficients for repeated errors, cognitive overload, and response latency against the rewards of knowledge gain. A 7-step algorithm for dynamic generation was implemented, featuring selective context window management and a multi-level pedagogical filter to ensure didactic correctness and term consistency. Results. Experimental verification was conducted within a web application for the “Data Analysis Basics” course over a 12-week period with 86 participants. The results demonstrated a statistically significant increase in learning outcomes. The experimental group, utilizing the dynamic generation algorithm, showed a knowledge gain of 23.8 %, compared to 8.9 % in the control group using a static chatbot. Furthermore, the average time required for a student to understand a complex concept was reduced from 12.7 to 7.4 seconds. The relevance matrix confirmed a high correlation between the calculated complexity level ct and the actual cognitive needs of the students. Scientific Novelty and Practical Significance. The scientific novelty lies in the synthesis of cognitive profiling, prompt orchestration, and a feedback loop that accounts for error structures and metacognitive reflection. The practical value is confirmed by the possibility of embedding the model into existing LMS/EdTech platforms, reducing the instructor’s routine workload, and enhancing the transfer of knowledge to new types of tasks. The study concludes that LLMs function not merely as information sources but as adaptive scaffolding tools for managing cognitive load in real-time.
Model of educational process personalization via LLM integration into a web application with dynamic explanation generation
Keywords: персоналізація навчання; великі мовні моделі; вебзастосунок; адаптивне пояснення; когні- тивний профіль; контекстне вікно; інтелектуальні системи навчання; генеративний ШІ; personalization of learning; large language models; web application; adaptive explanation; cognitive profile; context window; intelligent tutoring systems; generative AI